2013
DOI: 10.1111/eea.12121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetation on density thresholds of adult desert locust gregarization from survey data in Mauritania

Abstract: In the desert locust, Schistocerca gregaria (Forskål) (Orthoptera: Acrididae), the threshold density inducing the gregarization phenomenon has never been determined under natural conditions. The influence of environmental factors on this phenomenon has been studied mostly in controlled environments. Based on data collected during several years by the survey teams of the National Center for Locust Control in Mauritania, we analyzed the influence of locust density, vegetation cover, and vegetation status on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 29 publications
3
47
0
3
Order By: Relevance
“…One might conclude that when the gregarization process is engaged, the rain is not the best indicator of the presence of larvae. This seems consistent with what is known otherwise of the gregarization process, which happens more likely in clumpy and drying habitats (Boua€ ıchi et al, 1996;Despland et al, 2000;Cisse et al, 2013Cisse et al, , 2015. This is also consistent with the less strict ecological requirements of transiens and gregariouscompared to solitariousdesert locusts (Despland, 2005).…”
Section: North and South Differences In Light Of Water Availabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…One might conclude that when the gregarization process is engaged, the rain is not the best indicator of the presence of larvae. This seems consistent with what is known otherwise of the gregarization process, which happens more likely in clumpy and drying habitats (Boua€ ıchi et al, 1996;Despland et al, 2000;Cisse et al, 2013Cisse et al, , 2015. This is also consistent with the less strict ecological requirements of transiens and gregariouscompared to solitariousdesert locusts (Despland, 2005).…”
Section: North and South Differences In Light Of Water Availabilitysupporting
confidence: 89%
“…The resulting large databases – initially made for operational purposes and not for research – are exploited. They have already helped to better assess the distribution of these solitarious locust populations in the Sahara (Popov, ; Guendouz‐Benrima et al., ; Babah Ebbe, ; Piou et al., ) or to evaluate the population density at which gregarization could happen (Cisse et al., ). The objective of this study is to identify the respective roles of environmental and intrinsic factors explaining local and regional dynamics of solitarious and transiens population development in recession periods.…”
Section: Introductionmentioning
confidence: 99%
“…These results completely support the development of tools which help to guide surveys as soon and as spatially precisely as possible . They also support the development of indicators to decide on whether or not a situation needs to be controlled . In addition, our results support the importance of the quality of feedback information from the field to the funders.…”
Section: Discussionsupporting
confidence: 74%
“…In an alternative approach towards defining the locust density threshold for transformations to the gregarious stage, Cisse et al [2013] used field data from the RAMSES database for Mauritania from 2003 to 2011 to explore relations between locust density, phase status and vegetation, by investigating the influence of vegetation on the gregarization thresholds of the desert locust. They showed that the latter varied from 208 to 1525 adults ha-1, dependent upon vegetation cover and condition.…”
Section: Introductionmentioning
confidence: 99%